2021
DOI: 10.1101/2021.08.26.457827
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frameshifting at collided ribosomes is modulated by elongation factor eEF3 and by Integrated Stress Response regulators Gcn1 and Gcn20

Abstract: Ribosome stalls can result in ribosome collisions that elicit quality control responses, one function of which is to prevent frameshifting by the stalled ribosome, an activity that entails interaction of the conserved yeast protein Mbf1 with uS3 on colliding ribosomes. However, the full spectrum of factors that mediate frameshifting during ribosome collisions is unknown. To delineate such factors in the yeast Saccharomyces cerevisiae, we used genetic selections for mutants that either suppress or increase fram… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…Previous studies showed that an E3 ubiquitin ligase, Hel2, triggers the RQC pathway by ubiquitinating collided ribosomes stalled at positively charged amino acid sequences, such as poly-Arg or poly-Lys (Brandman et al, 2012; Houston et al, 2022; Ikeuchi et al, 2019; Matsuo et al, 2017; Matsuo et al, 2020). Ubiquitination leads to ribosome rescue but, in the absence of Hel2, collided ribosomes bypass these stall-inducing sequences and continue translating.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that an E3 ubiquitin ligase, Hel2, triggers the RQC pathway by ubiquitinating collided ribosomes stalled at positively charged amino acid sequences, such as poly-Arg or poly-Lys (Brandman et al, 2012; Houston et al, 2022; Ikeuchi et al, 2019; Matsuo et al, 2017; Matsuo et al, 2020). Ubiquitination leads to ribosome rescue but, in the absence of Hel2, collided ribosomes bypass these stall-inducing sequences and continue translating.…”
Section: Resultsmentioning
confidence: 99%
“…We obtained the original trm6-504 (Y200) and its WT parent (Y190) from Dr. James Anderson. The BY trm6-504 strain was reconstructed essentially as previously described (70), with three DNA components constructed in a plasmid vector: first, nt 893-1434 of the TRM6 coding sequence (containing the C1292G mutation of the trm6-504 mutant) and 204 nt of the 3’ UTR; second, K. lactis URA5 ; third, nt 1384-1434 of the TRM6 coding region. The DNA construct was removed from the vector, transformed into S. cerevisiae WT cells by linear transformation, confirmed by PCR, and then strains were plated onto media containing 5-FOA to select for Ura - cells obtained by homologous recombination, which were sequence verified.…”
Section: Methodsmentioning
confidence: 99%